Distinct roles of BRCA2 in replication fork protection in response to hydroxyurea and DNA interstrand cross-links - Rickman, Kimberly A. (Genes Dev, 2020)
DNA interstrand cross-links (ICLs) are a form of DNA damage that requires the interplay of a number of repair proteins including those of the Fanconi anemia (FA) and the homologous recombination (HR) pathways. Pathogenic variants in the essential gene BRCA2/FANCD1, when monoallelic, predispose to breast and ovarian cancer, and when biallelic, result in a severe subtype of Fanconi anemia. BRCA2 function in the FA pathway is attributed to its role as a mediator of the RAD51 recombinase in HR repair of programmed DNA double-strand breaks (DSB). BRCA2 and RAD51 functions are also required to protect stalled replication forks from nucleolytic degradation during response to hydroxyurea (HU). While RAD51 has been shown to be necessary in the early steps of ICL repair to prevent aberrant nuclease resection, the role of BRCA2 in this process has not been described. Here, based on the analysis of BRCA2 DNA-binding domain (DBD) mutants (c.8488-1G>A and c.8524C>T) discovered in FA patients presenting with atypical FA-like phenotypes, we establish that BRCA2 is necessary for the protection of DNA at ICLs. Cells carrying BRCA2 DBD mutations are sensitive to ICL-inducing agents but resistant to HU treatment consistent with relatively high HR repair in these cells. BRCA2 function at an ICL protects against DNA2–WRN nuclease–helicase complex and not the MRE11 nuclease that is implicated in the resection of HU-induced stalled replication forks. Our results also indicate that unlike the processing at HU-induced stalled forks, the function of the SNF2 translocases (SMARCAL1, ZRANB3, or HLTF), implicated in fork reversal, are not an integral component of the ICL repair, pointing to a different mechanism of fork protection at different DNA lesions.